Pluralisme Hukum dalam Sistem Kewarisan Anak Bungko: Dialektika Hukum Adat dan Hukum Islam di Masyarakat Pangkep - Maulidah, Tahani Asri; Kurniati; Ilyas, Musyfikah; Tahir, Juraeri; Idrus, Achmad Musyahid (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This study examines the inheritance distribution practice of the youngest child (anak bungko) in the Pangkep community from the perspective of legal pluralism between customary law and Islamic law. The main issue is the practice of granting a larger inheritance share to the youngest child, which does not fully conform to Islamic inheritance law. The research questions address the practice itself, societal and Islamic legal perspectives, and its implications for family justice. This study uses a qualitative method with a socio-legal approach based on literature review. The findings show that the larger share given to the youngest child is based on their social role in caring for parents and maintaining family continuity. While considered fair socially, it requires adjustment in Islamic law through grants and wills. This reflects a dynamic interaction between customary and Islamic law within legal pluralism.